ANALYSIS OF LIVER FUNCTION AND BIOCHEMICAL PARAMETERS OF FLUOROSIS AFFECTED RENAL FAILURE PATIENTS IN UDAYAGIRI MANDAL, NELLORE DISTRICT, A. P., INDIA - P. JAGANMOHAN; K. R. S. SAMBASIVA RAO; C. SRUJANA; S. V. L. NARAYANA RAO (The Bioscan, 2011)
The alcoholic leaf extract of the three Indian medicinal plants Annona squamosa, Aegle marmelos and Citrus limon were screened for its antimicrobial activity using disc diffusion method. They were tested against four gram positive bacteria (Staphylococcus aureus, Staphylococcus epidermidis, Bacillus cereus, Bacillus subtilis), three gram negative bacteria (Escherichia coli, Pseudomonas aeruoginosa, Klebsiella pneumonia) and against three fungi (Aspergillus niger, Aspergillus fumigates,Candida albicans). It was observed that all the three alcoholic leaf extracts showed antibacterial and antifungal activity. The alcoholic leaf extract of Annona squamosa was found to be most active against S. aureus, B. cereus, K. pneumonia, A. niger and A.fumigates. The alcoholic leaf extract of Aegle marmelos was found to be active against B. subtilis, E. coli, P.aeuroginosa and C. albicans. The alcoholic leaf extract of Citrus limon was most active against S.epidermidis and E. coli. The susceptibility of the microorganisms to the extracts of these plants was compared with each other and with the standard antibiotics ciprofloxacin and ketoconozole. The antimicrobial activities of the three alcoholic leaf extracts are discussed according to their phytochemical components. It is concluded that these three Indian medicinal plants may serve as a valuable source of compounds with therapeutic potential.